The Relationship Between Social Factors and Individual Well-Being: An Analysis of Mental and Physical Health in Social Dynamics - Warin, Araya Kanchanapisek (Journal of Social Science Studies, 2021)
This research aims to analyze the relationship between social factors and individuals' mental and physical health. Social factors such as social stigma, inequality in education, employment, and access to health services have a significant impact on individual well-being. The research concluded that social inequality contributes to a decrease in an individual's quality of life, both physically and psychologically. Strong social support and access to adequate education can improve individual health conditions. More inclusive policies that consider social factors in the provision of health and education services are needed to improve overall well-being. This research is expected to contribute to the development of fairer and more equitable community health policy.